Fractures of the knee in children—what can go wrong? A case file study of closed claims in the Patient Compensation Association covering 16 years. (October 2015) - Leeberg, V.; Sonne-Holm, S.; Krogh Christoffersen, J.; Wong, C.
Introduction: Intra-articular knee fractures in children are rare. The Patient Compensation Association (PCA) receives claims for financial compensation from patients who believe they have sustained damage from their treatment in the health care system. We used relevant cases of closed claims to identify causality and co-factors contributing to these apparent malpractices. Materials and methods: A partial root core analysis was performed on closed claims from the PCA database concerning proximal tibial fractures in children aged ≤15 years. Results: We identified 13 cases. The main complaint was missed diagnosis (6 cases)—fractures of the tibial eminence were the main culprit, with damage to the popliteal artery caused by a medial condyle fracture being the most serious. All cases were missed by junior doctors. Secondary complaints were problems with casting, dissatisfaction with correct treatment, and insufficient surgery or complications relating to surgery. Eight of the complaints were acknowledged, with six receiving financial compensation ranging from EUR 9, 600 to EUR 70, 000. Five out of the six cases of missed diagnosis were acknowledged. Conclusions: This study indicates that recognizing the degree of injury to the knee in children, which should include an X-ray examination, is key to preventing missed diagnosis and delayed and potentially more difficult surgery with long-lasting sequelae for the child. The PCA database seems to be a useful way to highlight systematic problems in the Danish health care system and could potentially be an important means to improving patient safety and preventing treatment-related injuries.